Beyond flavor: dietary vanillyl alcohol, a D₂ receptor antagonist promoting sleep - Lijing Zhang; Yujie Yang; Dongmei Yang; Richard Ward; Zhenshuai Hu; Hao Chen; Mengli Lan; Cheng Xiang; Su An; Jiameng Dai; Ying Zhu; Xianrun Sun; et al. (Food Research International, 2026)

Mechanistic insights into the adsorption and separation of nonpolar molecules on delocalization porous carbon: Dispersion interactions enhanced by multiple bonds - Peixin Wang; Jingxu Tian; Da Wei; Yue Sun; Bo Liu; Wenji Pi; Jun Ma; Yunfeng Zhang; Hongyu Chen; Rui Shi; Yang Guo; Xiang Xu; et al. (Chemical Engineering Journal, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Transcriptome and metabolome analysis reveals that cuproptosis in bovine cumulus cells triggers the intercellular transmission of senescence and mitochondrial dysfunction to impair oocyte quality - Hong Xu; Tian Tian; Dan Xu; Xiaoxue Du; Rui Su; Jinghong Liang; Ying Liu; Yuqing Zhang; Chang Liu; Shuang Liang; Qingying Li; Deli Ding; et al. (Theriogenology, 2026)

Sex-specific associations between prenatal PM2.5 exposure and reproductive hormone levels in offspring aged 1–2 years: A prospective birth cohort study - Wenpu Shao; Shengli Jiang; Yudiyang Ma; Ning Chen; Zhiping Niu; Rui Tang; Meiqi Xing; Lei Zheng; Xinru Zhao; Bin Sun; Haibo Li; Ziyi Zhou; et al. (Environmental Research, 2026)

Molten salt-assisted gasification unlocks graphitic nitrogen dominated porous carbons from biomass for high-performance zinc–air batteries - Yiwen Chen; Yangyang Chen; Changrong Zhong; Rui Liu; Gangyong Li; Yucan Zhu; Zhi Li; Minjie Zhou; Rui Tian; Binhong He; Wenyuan Xu (Bioresource Technology, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Underground mine tunnel fire dynamics: Experimental investigation and AI-driven characterization of flame behavior - Jingmin Xu; Rui Tian; Ashish Kakoria; Aamir Iqbal; Tao Yang; Lina Zheng; Guang Xu (Tunnelling and Underground Space Technology, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Efficient photocatalytic degradation of acetamiprid via Fe2O3/Fe-TCBPE activating peroxymonosulfate - Chenchen Li; Zhourui Wu; Rui Xu; Tai Xiang; Lin Tian; Yong Zhang (Journal of Environmental Sciences, 2026)

Experimental study on seismic behaviour of full-scale glued laminated timber frame-glass wall composite structural unit - Tian Xia; Tao Zhou; Rui Xu; Hao Huang; Shao-Bo Kang (Engineering Structures, 2026)

PD-1⁺ CD8⁺ T cells: roles of PD-1 beyond an exhaustion marker - Jingyi Chen; Zixiang Chen; Liangjie Xu; Jieting Jia; Ke Rui; Jie Tian (Seminars in Immunopathology, 2026)

A nationwide analysis of hospitalised patients with lower respiratory infections in China: life-stage-specific pathogen spectra, co-detection networks, and sex disparities - Yamin Sun; Min Wang; Tian Qin; Jue Liu; Jiale Yuan; Pei Li; Xinchang Lun; Zhigang Wang; Linghang Wang; Rui Song; Xi Wang; Ronghua Jin; et al. (Science Bulletin, 2026)

Bridging training–projection gaps in purely data-driven deep learning for runoff under climate change - Yiting Cen; Bin Yu; Rui Xiong; Mengqian Lu; Yong Tian; Feng Han; Peng Xu; Yi Zheng (Journal of Hydrology, 2026)

Underestimation of industrial contributions to VOC fluctuation in the Hangzhou Bay: Insights from simultaneous measurements and ML-SHAP analysis - Kun Hu; Song Guo; Lei Shen; Zichao Wan; Xinshi Ni; Rui Tan; Xudong Tian; Bingye Xu; Limin Zeng; Qingyan Fu; Min Hu; Sihua Lu (Environmental Pollution, 2026)

Spatial and environmental niche differentiation facilitates sympatric macaques' coexistence in montane-canyon landscapes: Implications for conservation - Wei Zhou; Yuan Wang; Deyan Ge; Qisen Yang; Gang Song; Jilong Cheng; Tian Tian; Yu Zhang; Jinbo Xu; Ying Liu; Weibo Wang; Xiaochuan Wang; et al. (Biological Conservation, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Dexmedetomidine regulates fatty acid oxidation through the AMPK/PGC-1α/CPT1A pathway to mitigate renal ischaemia-reperfusion injury - Cong-Li Zhang; Yan Yan; Ke Wang; Jun-Jie Ma; Wen-Jun Xu; Gang Liu; Xing-Chun Zhu; Zhi-Gao Zhu; Hao-Feng Ding; Zi-Rui Ke; Kai Yao; Fang-Tian Fan; et al. (Toxicology and Applied Pharmacology, 2026)

Mutual information and adaptive sparse learning for long term closed loop prediction of ship manoeuvring - Rui Tian; Xiufeng Zhang; Haitong Xu; C. Guedes Soares; Xiuwen Liu (Ocean Engineering, 2026)

Data-driven ship manoeuvring modelling for long-term trajectory prediction using the progressive optimised identification framework - Rui Tian; Xiufeng Zhang; Haitong Xu; C. Guedes Soares; Xiuwen Liu; Zhan Cheng (Ocean Engineering, 2026)

Minute‐Scale Adsorption of Diverse Marine Viruses Onto Clay Minerals - Lanlan Cai; Yuan Tian; Xuan Qiu; Yongle Xu; Hailiang Dong; Rui Zhang (Environmental Microbiology, 2026)
Viruses are ubiquitous biological entities with important roles in microbial mortality, genetic exchange and biogeochemical cycles. Clays, the most abundant mineral constituents on Earth, function as highly effective adsorbents for viruses, critically modulating their environmental persistence and ecological impact. However, the mechanisms and environmental drivers governing virus–clay interactions remain poorly understood. This study systematically investigates the adsorption kinetics of nine marine viruses onto a clay mineral (smectite, NAu‐2) under environmentally representative conditions. Viruses isolated from distinct hosts (heterotrophic bacteria, cyanobacteria and eukaryotic algae) and exhibiting diverse morphological features (myovirus, siphovirus, podovirus and tailless virus) were evaluated across gradients of NAu‐2/virus concentrations, pH, temperature and ionic strength. Elevated NAu‐2 concentrations (> 50 mg/L) induced rapid and near‐complete virus adsorption (90%–99%) within 1 min, while low concentrations (0.1–10 mg/L) yielded efficiencies from negligible to > 50%. Adsorption dynamics showed minimal correlation with viral morphology and instead depended on physicochemical properties. Electron microscopy revealed preferential viral localization at edge sites of NAu‐2, driven by charge heterogeneity from protonated alumina‐oxygen octahedra. These findings provide quantitative information on virus–clay interactions and offer key insights into the availability, transport and fate of viruses in the environment, paving the way for more accurate parameterization of biogeochemical cycling across ecosystems.

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

Chang’e-6 lander reveals local hour-scale temporal variations in lunar surface water - Honglei Lin; Heng-Ci Tian; Sheng Gou; Wei Yang; Jinning Li; Li Liu; Kai Fan; Sen Hu; Rui Xu; Zhiping He; Yong Wei; Yangting Lin (Science Bulletin, 2026)

Ship manoeuvring motion modelling based on dual-criterion feature selection and data augmentation - Rui Tian; Xiufeng Zhang; Haitong Xu; C. Guedes Soares; Xiuwen Liu (Ocean Engineering, 2026)

Highly crystalline poly(heptazine imide) with improved intra- and inter-plane charge transport for efficient photocatalytic degradation of gaseous acetaldehyde - Dongying Wang; Lei Zhang; Rui Tian; Junjie Xu; Shuhao Sun; Beibei Cai; Ruijie Sun; Fei He (Chemical Engineering Journal, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

High-value utilization of chromium ore processing residue (COPR) through corn straw-soda roasting followed leaching processes - Cheng Tian; Zilong Li; Cunfang Lu; Rui Xu; Min Zhang; Lin Yang; Wenlin Xie; Zhengnan Zhong; Yuanyuan He; Juan Wen; Dan Luo (Journal of Environmental Chemical Engineering, 2026)

A Cu-based catalytic molecularly imprinted electrochemical sensor on paper for phthalylsulfacetamide detection in environmental water - Shuyan Miao; Jing Zhou; Zhen Xu; Yuting Wang; Rui Liu; Tian Gan (Journal of Environmental Chemical Engineering, 2026)

Relationship between expression of derived factor-1CXC chemokine receptor 4 in tumor tissues of patients with non-small cell lung cancer and postoperative lymph node metastasis - Zhanwu Zhang; Xiaoming Wang; Rui Tian; Kunpeng Duan; Xu Zhang (Journal of Molecular Histology, 2026)

Effects of purple corn anthocyanins on feed intake, body weight, antioxidant activity, lipid metabolism, rumen fermentation, and rumen microbiota and function in perinatal goat does - Qi Lu; Yiqing Xu; Jixiao Qin; Shuanglong Xie; Rui Chen; Yiming Ban; Chengcheng Gao; Peiyao Li; Xu Wang; Xingzhou Tian (Animal Feed Science and Technology, 2026)

Synergistic recovering Fe, Al and biochar through biomass-reduction alkali roasting and wet magnetic separation for red mud (RM): behavior and mechanism - Rui Xu; Cunfang Lu; Min Zhang; Cheng Tian; Dan Luo; Lin Yang; Wenlin Xie; Zhengnan Zhong; Juan Wen (Minerals Engineering, 2026)

Insight into cryopreservation mechanism of natural deep eutectic solvents (NADESs) from the transcriptomics perspective - Rui Hu; Da-Wen Sun; You Tian; Liang Xu; Libin Sun (Chemical Engineering Journal, 2026)

Research progress on quorum-quenching strategies for membrane biofouling control - Hongwei Wu; Kuo Yang; Yifan Gao; Rui Xu; Yuzhang Feng; Yinning Wang; Huimin Lin; Siqi Hu; Gege Tian; Jiaying Li; Pingfeng Yu; Bing Zhang (ENGINEERING Environment, 2026)

A new strategy to simulate daily spatial distributions of urban air pollutants based on land use regression in Wuhan, China - Ya Tian; Gang Xu; Rui Xiao; Hui Lin (Atmospheric Pollution Research, 2026)

Phosphorus fertilization shapes rhizosphere beneficial microbial communities and soil–plant relations in arid cotton fields of Xinjiang, China - Bin Peng; Shuai Zhao; Cong-Rui Liu; Wen-Xuan Mai; Na Zhou; Ping Zhang; Shu-Ying Wang; Xu Liu; Bao-Zhan Wang; Chang-Yan Tian (Plant and Soil, 2026)

Diagnostic Value of Fast Stroke Imaging for Salvageable Brain Tissue and Collateral Circulation in Stroke Patients - Dongxue Wang; Shuang Liang; Zhongzhen Yue; Ye Tian; Jing Zhang; Liyu Qiao; Rui Li; Junqiang Xu; Rui Chen; Fanxiang Meng; Yichao Wang (Journal of Medical and Biological Engineering, 2026)

Grassland soil seed bank responses to grazing exclusion: a global synthesis - Jishuai Su; Lixin Yu; Rui Tian; Wanbing Liu; Ruolin Zhao; Menghan Niu; Zekai Yang; Yi Zhang; Fengwei Xu; Heyong Liu; Yong Jiang (Journal of Environmental Management, 2026)

Iron-driven synergism among microbial functional taxa facilitates recovery from denitrification toxicity - Yongzhi Zhang; Xiaoxiao Li; Linjun Gao; Ping Ye; Rui Wang; En Zhou; Tian Sun; Miaoqing Xu; Rui Wan; Xiang Li (Journal of Environmental Management, 2026)

Efficient oxygen evolution in acidic electrolysis of water using copper loaded with iridium nanoclusters - Yanan Song; Bingxin Zhang; Tai Xiang; Huabin Wang; Yong Zhang; Xiaoning Tang; Lin Tian; Rui Xu (Journal of Environmental Sciences, 2026)

Curcumin Ameliorates Depressive-like Behaviors by Modulating mGluR2/PGC-1α-Mediated Glutamatergic Homeostasis and Mitochondrial Function - Liping Xu; Deyun Jiang; Lujing Yang; Conghua Ji; Rong Bai; Yirun Xu; Tian-Rui Xu (Molecular Neurobiology, 2026)

Ship manoeuvring model identification using mutual information clustering with stepwise regression structural optimisation under small-sample constraints - Xiufeng Zhang; Rui Tian; Haitong Xu; Xiuwen Liu; C. Guedes Soares (Ocean Engineering, 2025)

Whole-genome resequencing unveils the phylogeographic coevolution of Oncomelania hupensis with Yangtze River dynamics in China - Lei Duan; Fang Luo; Qin Liu; Shen Chen; Xia Tian; Wen-Wen Lv; Lu He; Zi-Rui Ren; Jing Xu; Xiao-Nong Zhou; Shi-Zhu Li; Shan Lv; et al. (Molecular Phylogenetics and Evolution, 2025)

Recent advances in manganese-based materials for water remediation: Multipollutant adsorption and catalytic oxidation - Hanghang Wang; Guangfei Qu; Yingying Cai; Chenyang Yin; Yaxin Tian; Rui Xu; Xinxin Liu; Minjie He; Changyi He; Jiao Wei (Environmental Research, 2025)

CRP and HNF1A collaborate to regulate the progression of laryngeal cancer through the Wnt signaling pathway - Zhigang Zhao; Xiaojing Zhu; Jinyuan Xu; Penglong Song; Yanan Sun; Zhenming Yang; Li Wang; Jiarui Zhang; Rui Zhao; Xiaoxue Chen; Wenjing Li; Linli Tian; et al. (Functional & Integrative Genomics, 2025)

Immobilization of arsenic and antimony by silica-Fe (hydr)oxides composite: investigation of potential ecological effects on the soil microbial environment - Rui Xu; Yaxin Tian; Qian Li; Guangfei Qu; Lang Liao; Zhe Yin; Zhenguo Wu; Yuqi Han; Yan Zhang; Yongbin Yang; Dongbin Liu; Haiyan Yan; et al. (Environmental Geochemistry and Health, 2025)

Dose effects of polyethylene microplastics on the degradation of phenanthrene in agricultural soils and its underlying mechanisms - Chengyue Liang; Weilian Fu; Lin Tian; Wumei Xu; Yong Zhang; Tai Xiang; Rui Xu (Journal of Environmental Chemical Engineering, 2025)

Self-healing sodium alginate-PEDOT:PSS conductive hydrogel for accelerated burn wound healing and real-time monitoring - Xinshuo Liu; Feng Chen; Yifan Zhang; Zexiang Zheng; Rui Huang; Jinhuan Tian; Hong Li; Changren Zhou; Shuyun Zhang; Huihua Xu; Lihua Li (Chemical Engineering Journal, 2025)

Global response of soil phosphatase activity to land reclamation and vegetation restoration - Huaisong Wang; Mingming Wang; Jialing Xu; Yibo Tian; Jinyu Bai; Lei Zhang; Lianxuan Shi; Jixun Guo; Yingzhi Gao; Rui Guo; Tao Zhang (CATENA, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

B2G: A novel framework for froth velocity estimation and quantification with graph neural networks - Rui Tian; Ziqi Lv; Xiu Liu; Meijie Sun; Yanan Tu; Zhiqiang Xu; Weidong Wang (Minerals Engineering, 2025)

Earthworms mitigate drought effects on microbial decomposition of straw under varying microplastic conditions - Chuanxiong Huang; Weijie Zhao; Hangle Ren; Rui Wu; Ying Liu; Hongxin Xu; Benhua Sun; Jianglan Shi; Xiaohong Tian; Rui Yin (Journal of Hazardous Materials, 2025)

Using Interactive Multi-Media Panorama Virtual Reality to Balance Heritage Science, Education and Conservation At Zhoukoudian, Fangshan UNESCO Global Geopark - Jun-Ting Qiu; Tong-Yu Zhang; Lixian Tian; Xin-Min Rui; Hong-Xu Mu; Liang Qiu; Long-Xin Xu (Geoheritage, 2025)

Dietary Houttuynia cordata Thunb. extract supplementation influences on antioxidant enzymes, meat quality, and gene expressions in fresh rabbit Longissimus thoracis et lumborum meat - Xu Wang; Shuanglong Xie; Rui Chen; Jixiao Qin; Yiqing Xu; Chao Ban; Qi Lu; Xingzhou Tian (Meat Science, 2025)

Rising disparities in grain self-sufficiency across China: Provincial divergence amidst overall national improvement - Xiaoyu Yu; Rui Xiao; Zhonghao Zhang; Feng Zhou; Fei Mo; Zhenci Xu; Feng Tian; Zhi Gao; Yansheng Li; Peng Zhu; Kailiang Yu; Lumeng Liu; et al. (Environmental Impact Assessment Review, 2025)

Functional shift in soil microbiome with decline in photosynthetic carbon input signifies rapid decrease of soil organic carbon during alpine grassland degradation - Minghua Song; Rui Pang; Yuqiang Tian; Yikang Li; Guiqiang Wang; Xingliang Xu (Biology and Fertility of Soils, 2025)

Identification of key genes linking bisphenols exposure and breast cancer - Zhen Wang; Meng Cao; Tian Gao; Xinyue Xu; Weihua Yu; Jiangzheng Liu; Rui Liu; Xiaodi Zhang; Fei Li; Chunxu Hai (Toxicology, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Hydrogel-elastomer hybrid integrated with radiative and evaporative cooling for passive temperature-adaptive regulation - Libin Sun; Da-Wen Sun; Liang Xu; You Tian; Rui Hu; Zhiwei Zhu (Chemical Engineering Journal, 2025)

The tumor suppressor SALL2 opposes chemotherapeutic resistance in breast cancer - Qiji Li; Chenxin Li; Yuhao Zhang; Zihan Zheng; Yun Wang; Yingqian Yang; Qingqing Zhu; Rui Wang; Wanhui Xu; Chengming Zhu; Qin Tian; Meng Wang; et al. (Molecular and Cellular Biochemistry, 2025)

Evaluating the Centre‐Periphery Hypothesis Through Genomic Phylogeographical Comparisons of Two Sister Species of Liquidambar in East Asia's Tertiary Relict Forests - Tian‐Rui Wang; Wu‐Qin Xu; Hans‐Peter Comes; Xin‐Yi Zhang; Jun Chen; Yin‐Gang Li; Ying‐Xiong Qiu (Journal of Biogeography, 2025)
Aim Understanding the spatial distribution of genetic variation within species is a central tenet in evolutionary biology and conservation biology. This study explores how historical demographic processes and/or environmental factors interact to affect contemporary genetic variation and adaptive potential, with a specific focus on testing the ‘centre‐periphery’ hypothesis (CPH). Location Subtropical China. Taxon Liquidambar. Methods We combined comparative phylogeography, landscape genomics and niche modelling to investigate the interplay between demographic history and past/current environmental factors in shaping genetic variation in Liquidambar formosana and L. acalycina , a sister pair of East Asia's Tertiary relict forests. Results In both species, core populations occupied highly suitable habitats at highest densities. Consistent with the CPH, population genetic diversity decreased, and differentiation increased, from centre to margin in L. acalycina , but not in L. formosana , likely reflecting different demographic histories and different relative contributions of geography, past (LGM) and current climates to their present‐day genetic variation. In addition, L. formosana showed higher adaptive potential to future climate change than L. acalycina . Main Conclusions This study demonstrates that differences in contemporary genetic variation and adaptability among closely related species can be explained by contrasting demographic responses to multiple geographic/climatic factors. In turn, it should also expand our understanding of the CPH, while informing future conservation efforts for these two study species.

Grazing and Enclosure Alter the Vertical Distribution of Bacterial Communities in Different Microhabitats of Wetlands Along the Xilin River - Xiaoai Cao; Yating Tian; Huamin Liu; Hongbo Yu; Feng Niu; Rui Zhang; Zhichao Xu; Yi Zhuo; Lu Wen; Dongwei Liu; Lixin Wang (Wetlands, 2025)

Identifying spatial drivers of soil heavy metal pollution risk integrating positive matrix factorization, machine learning, and multi-scale geographically weighted regression - Yujie Pan; Anmeng Sha; Wenjing Han; Chang Liu; Guowangchen Liu; Emily Welsch; Min Zeng; Shasha Xu; Yi Zhao; Shang Tian; Yiyi Li; Rui Deng; et al. (Journal of Hazardous Materials, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Taloring sawdust derived hydrochar via red mud for cadmium removal: Electron transfer insight and recyclability assessment - Ting Cui; Dingxiang Chen; Ran Duan; Fan Yang; Danting Li; Lin Tian; Yong Zhang; Huabin Wang; Rui Xu (Chemosphere, 2025)

Chicken adipose tissue is differentially involved in primary and secondary regional immune response to NDV through miR-20a-5p-NR4A3 pathway - Yi Jiang; Rui Zhang; Xinxin Xu; Xiangnan Wang; Yufei Tian; Wei Zhang; Xiaoli Ma; Chaolai Man (Veterinary Immunology and Immunopathology, 2025)

Improvement of ecological structure and function in phosphorus tailings-based soils through phosphorus-solubilizing bacteria inoculation and magnetic field treatment - Caiyue Jin; Xinxin Liu; Bangjin Chen; Guangfei Qu; Yaxin Tian; Fenghui Wu; Jieqian Yang; Rui Xu; Ping Ning (Journal of Environmental Chemical Engineering, 2025)

Radio frequency inactivation of Bacillus cereus and natural microbiota in brown rice: Evaluation of inactivation kinetics and germination capacity - Gaoji Yang; Dingting Zhou; Juanjuan Xu; Yingqi Tian; Rui Li; Shaojin Wang (Food Control, 2025)

Sleep deprivation stimulates adaptive thermogenesis by activating AMPK pathway in mice - Tian-Shu Zheng; Xin-Ran Gao; Rui-Ping Xu; Yi-Fei Zhao; Zhi-Teng Yang; De-Hua Wang (Journal of Comparative Physiology B, 2025)

Underwater Target Detection with High Accuracy and Speed Based on YOLOv10 - Zhengliang Hu; Le Cheng; Shui Yu; Pan Xu; Peng Zhang; Rui Tian; Jingqi Han (Journal of Marine Science and Engineering, 2025)
Underwater target detection exhibits extensive applications in marine target exploration and marine environmental monitoring. However, conventional images of underwater targets present challenges including blurred contour information, complex environmental conditions, and pronounced scattering effects. In this work, an underwater target detection method based on YOLOv10 is designed, and the detection performance is compared with the YOLOv5 model. Experimental results demonstrate that the YOLOv10 model has a mAP50 of 85.6% on the URPC 2020 dataset, improving the mAP50 by 1.2% than that of YOLOv5. This model exhibits high detection accuracy and high proceeding speed, which provides a promising support for precise and fast underwater target detection.

An effective strategy for high-value utilization of chromite ore processing residue (COPR) through reductive alkali roasting and physical separation - Cheng Tian; Cunfang Lu; Jun Yang; Rui Xu; Min Zhang; Juan Wen; Yelei Wang; Shuo Zhang; Yuanyuan He; Dan Luo; Huazheng Luo; Xingran Zhang (Process Safety and Environmental Protection, 2025)

Numerical investigation on the suction caisson response considering seabed trenches and cyclic loading - Le Wang; Tingran Zhang; Xinglei Cheng; Wanhai Xu; Zhichao Shen; Shengjie Rui; Yinghui Tian (Ocean Engineering, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

A combined strategy of brain neuroprotection and endogenous neuroregeneration for enhanced intracerebral hemorrhage treatment via an injectable biomimetic hydrogel with efficient ROS scavenging and therapeutics delivery - Jiake Xu; Luyao Wan; Xueqi Wang; Yang Wei; Yinhai He; Shenglan You; Rui Zhong; Chengwei Wang; Hao Li; Chao You; Meng Tian (Chemical Engineering Journal, 2025)

A fidelity evaluation model for watermarked vector maps based on improved fuzzy comprehensive evaluation and random forest - Xu Xi; Huimin Tian; Jinglong Du; Mingkang Wu; Rui Huang (Earth Science Informatics, 2025)

SOTHE: SOlar-terrestrial habitability explorer - Jiajia Liu; Bingkun Yu; Fuchuan Pang; Siteng Fan; Lixiang Gu; Lingping He; Yajuan Lei; Bo Li; Rui Li; Yiren Li; Dongdong Liu; Kai Liu; et al. (Advances in Space Research, 2025)

Higher water content observed in smaller size fraction of Chang'e-5 lunar regolith samples - Honglei Lin; Rui Xu; Shuai Li; Rui Chang; Hejiu Hui; Yang Liu; Hengci Tian; Kai Fan; Zhiping He; Huaiyu He; Wei Yang; Yangting Lin; et al. (Science Bulletin, 2024)

Instability of natural deep eutectic solvents (NADESs) induced by Amadori rearrangement and its effects on cryopreservation of yeast cells - Rui Hu; Da-Wen Sun; You Tian; Liang Xu; Libin Sun (Food Chemistry, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Study of the effect of keap1 on oxidative stress in human umbilical cord mesenchymal stem cells - Hongrong Deng; Yunxia Chen; Huiwen Liu; Li Wang; Hao Xu; Bin Tan; Qin Yi; Rui Wang; Bolin He; Jie Tian; Jing Zhu (Molecular Biology Reports, 2024)
Background HucMSCs had shown promising efficacy in treating childhood diseases, but oxidative stress induced by the poor microenvironment at the site of damage resulted in low cell survival after transplantation, thus preventing the cells from maximizing therapeutic efficacy. Therefore, this study aimed to investigate the role and mechanism of keap1 in oxidative stress injury of human umbilical cord mesenchymal stem cells (hucMSCs), and to provide theoretical support for improving the efficacy of stem cell therapy. Methods The hucMSCs were treated with hypoxic low-sugar-free serum (GSDH) to mimic the damaged site microenvironment after implantation. Adenoviral overexpression of keap1 gene of hucMSCs was performed in vitro, and cell proliferation ability was detected by CCK8 assay, crystal violet staining assay, and cell cycle assay. Cellular redox level was assessed by Amplex Red, MDA, and GSH/GSSG kit. Mitochondrial morphology was evaluated by mitotracker Red staining. ATP production was estimated by ATP detection kit. The mRNA and protein expression levels were tested by western blotting and RT-qPCR. Results GSDH treatment substantially upregulated keap1 expression. Subsequently, we found that overexpression of keap1 notably inhibited cell proliferation and caused cells to stagnate in G1 phase. At the same time, overexpression of keap1 induced the production of large amounts of H 2 O 2 and the accumulation of MDA, but suppressed the GSH/GSSG ratio and the expression of antioxidant proteins NQO1 and SOD1, which caused oxidative stress damage. Overexpression of keap1 induced cells to produce a large number of dysfunctional mitochondria resulting in reduced ATP production. Moreover, Overexpression of keap1 significantly decreased the IKKβ protein level, while upregulating IkB mRNA levels and downregulating P50 mRNA levels. Conclusions Overexpression of keap1 may induce oxidative stress injury in hucMSCs by down-regulating IKKβ expression and inhibiting NF-κB pathway activation. This implies the importance of keap1 in hucMSCs and it may be a potential gene for genetic modification of hucMSCs.

On the Nearshore Significant Wave Height Inversion from Video Images Based on Deep Learning - Chao Xu; Rui Li; Wei Hu; Peng Ren; Yanchen Song; Haoqiang Tian; Zhiyong Wang; Weizhen Xu; Yuning Liu (Journal of Marine Science and Engineering, 2024)
Accurate observation of nearshore waves is crucial for coastal safety. In this study, the feasibility of extracting wave information from wave video images captured by shore-based cameras using deep learning methods was explored, focusing on inverting nearshore significant wave height (SWH) from instantaneous wave video images. The accuracy of deep learning models in classifying wind wave and swell wave images was investigated, providing reliable classification results for SWH inversion research. A classification network named ResNet-SW for wave types with improved ResNet was proposed. On this basis, the impact of instantaneous wave images, meteorological factors, and oceanographic factors on SWH inversion was evaluated, and an inversion network named Inversion-Net for SWH that integrates multiple factors was proposed. The inversion performance was significantly enhanced by the specialized models for wind wave and swell. Additionally, the inversion accuracy and stability were further enhanced by improving the loss function of Inversion-Net. Ultimately, time series inversion results were synthesized from the outputs of multiple models; the final inversion results yielded a mean absolute error of 0.04 m and a mean absolute percentage error of 8.52%. Despite certain limitations, this method can still serve as a useful alternative for wave observation.

Probiotic nucleotides increase IL-10 expression in airway macrophages to mitigate airway allergy - Jinmei Xue; Zhizhen Liu; Bailing Xie; Rui Dong; Juan Wu; Yisha Wu; Zhihan Xu; Yuhe Tian; Yao Wei; Zhigang Geng; Lei Lu; Yu Liu; et al. (Inflammation Research, 2024)

Iron-based materials for immobilization of heavy metals in contaminated soils: A critical review - Yaxin Tian; Guangfei Qu; Rui Xu; Xinxin Liu; Caiyue Jin (Journal of Environmental Chemical Engineering, 2024)

Effects of Different Concentrations of Weak Acid Fracturing Fluid on the Microstructure of Coal - Gan Rui; Zuo Shaojie; Si Junting; Liu Chengwei; Tian Feng; Jiang Zhizhong; Wang Changwei; Peng Shouqing; Xu Zhiyuan (Natural Resources Research, 2024)

Decoding polyphenol metabolism in patients with Crohn’s disease: Insights from diet, gut microbiota, and metabolites - Liyuan Xiang; Shuyu Zhuo; Wanrong Luo; Chunyang Tian; Shu Xu; Xiaozhi Li; Yijun Zhu; Rui Feng; Minhu Chen (Food Research International, 2024)

MARCH1 and MARCH2 inhibit pseudorabies virus replication by trapping the viral cell-to-cell fusion complex in trans-Golgi network - Rui Huang; Cui-Hong Rao; Yuan-Zhe Bai; Changqing Yu; Meng Chen; Jin-Mei Peng; Shi-Jia Xu; Yue Sun; Meng Fandan; Chuang Lyu; Mirwaise Khan; Tong-Qing An; et al. (Veterinary Microbiology, 2024)

Developing effective radio frequency drying processes for tiger nuts: Dynamic analysis of moisture state, dielectric properties and quality - Mengge Li; Yingqi Tian; Longlong Jiang; Juanjuan Xu; Rui Li; Shaojin Wang (Journal of Food Engineering, 2024)

Engineering disease-resistant plants with alternative translation efficiency by switching uORF types through CRISPR - Jingjing Tian; Zhijuan Tang; Ruixia Niu; Yulu Zhou; Dan Yang; Dan Chen; Ming Luo; Rui Mou; Meng Yuan; Guoyong Xu (Science China Life Sciences, 2024)

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

Micronutrient perspective on COVID-19: Umbrella review and reanalysis of meta-analyses - Yafei Xie; Jianguo Xu; Dan Zhou; Mingyue Guo; Mengxiang Zhang; Ya Gao; Ming Liu; Jiyuan Shi; Kelu Yang; Qingyong Zheng; Liang Zhao; Yu Qin; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Effect of volatile compounds produced by Weissella cibaria BWL4 on Botrytis cinerea infection in fruit and complete genome sequence analysis of BWL4 - Danfeng Zhang; Xuehua Xu; Xinrui Tian; Rui Wang; Tingting Hu; Wei Shi; Wanling Bi; Yingwang Ye (Postharvest Biology and Technology, 2024)

A NIR-II quantum dot-assisted dual-color imaging strategy enables simultaneous tracking of two subtypes of extracellular vesicles in vivo - Xing-Chi Liu; He-Jing Zhang; Rui Xu; Jing Liu; Hou-Fu Xia; Qi-Hui Xie; Zhi-Quan Tian; Zi-Li Yu; Gang Chen (Chemical Engineering Journal, 2024)

Qualitative classification of waste garments for textile recycling based on machine vision and attention mechanisms - Rui Tian; Ziqi Lv; Yuhan Fan; Tianyu Wang; Meijie Sun; Zhiqiang Xu (Waste Management, 2024)

Synergistic effects of Co-pyrolysis on the immobilization and transformation of lead (Pb), chromium (Cr), nickel (Ni), and fluorine (F) in phosphogypsum-biomass mixtures - Minjie He; Rui Xu; Guangfei Qu; Xianyu Fu; Xinxin Liu; Hanghang Wang; Yaxin Tian; Chenyang Yin (Journal of Environmental Management, 2024)

Chitosan-based injectable hydrogel with multifunction for wound healing: A critical review - Aiqin Li; Bin Ma; Shiyao Hua; Rui Ping; Lu Ding; Bingren Tian; Xu Zhang (Carbohydrate Polymers, 2024)

Assessing ammonium pollution and mitigation measures through a modified watershed non-point source model - Feng Han; Qing Tian; Nengwang Chen; Zhaoping Hu; Yao Wang; Rui Xiong; Peng Xu; Wei Liu; Alejandra Stehr; Ricardo O. Barra; Yi Zheng (Water Research, 2024)

Insights into the generation of multiple reactive species in UV254/PMS/I− system and their roles for degradation of phenolic and non-phenolic pollutants - Zhen Tian; Yiyang Li; Lina Wang; Rui Xu; Aihua Wei; Jun He; Chengjun Wang (Journal of Water Process Engineering, 2024)

Dual-bioinspired and ultra-flexible photothermal eutectogels for highly efficient passive anti-freezing - You Tian; Da-Wen Sun; Liang Xu; Libin Sun; Rui Hu (Chemical Engineering Journal, 2024)

Highly thermally conductive composites with boron nitride nanoribbon array - Peng Wei; Lei Feng; Qiang Chen; Zhijie Dong; Qiang Song; Rui Tian; Ruoxi Zhang; Liyuan Guo; Dongfang Xu; Mengdan Hou; Haojie Song (Chemical Engineering Journal, 2024)

DeepWMH: A deep learning tool for accurate white matter hyperintensity segmentation without requiring manual annotations for training - Chenghao Liu; Zhizheng Zhuo; Liying Qu; Ying Jin; Tiantian Hua; Jun Xu; Guirong Tan; Yuna Li; Yunyun Duan; Tingting Wang; Zaiqiang Zhang; Yanling Zhang; et al. (Science Bulletin, 2024)

Fly ash-dominated High-Strength Engineered/Strain-Hardening Geopolymer Composites (HS-EGC/SHGC): Influence of alkalinity and environmental assessment - Jian-Cong Lao; Rui-Yang Ma; Ling-Yu Xu; Yang Li; Yi-Nong Shen; Jie Yao; Yan-Shuai Wang; Tian-Yu Xie; Bo-Tao Huang (Journal of Cleaner Production, 2024)

Multi-hazard stochastic response analysis and reliability evaluation of a 5 MW monopile offshore wind turbine based on extended platform FAST-S - Yazhou Xu; Rui Tian; Jing Duan; Yanqiong Ding; Hui Zhang (Engineering Structures, 2024)

A modified Chebyshev collocation method for the generalized probability density evolution equation - Rui Tian; Yazhou Xu (Engineering Structures, 2024)

The isomorphous substitution of Si(4Al) with P in FAU zeolite and its stabilization effect - Qiang Zhang; Hongjuan Zhao; Xingyu Liu; Rui Li; Tian Xia; Yue Ma; Yuren Wang; Kang Chen; Jiujiang Wang; Penghui Zeng; Honghai Liu; Chaowei Liu; et al. (Chemical Engineering Journal, 2024)

Analysis of landslide deformation in eastern Qinghai Province, Northwest China, using SBAS-InSAR - Haibo Tian; Pinglang Kou; Qiang Xu; Yuxiang Tao; Zhao Jin; Ying Xia; Jiangfan Feng; Rui Liu; Yongcheng Gou (Natural Hazards, 2024)

An efficient synthesis and organic-modification coupling strategy to produce highly dispersed ultrathin antioxidant intercalated layered double hydroxides for enhancing performance of polypropylene composites - Zijia Li; Menghua Zhao; Rui Tian; Yalin Shi; Weiliang Tian; Yiqing Bai; Meng Xu; Kai Xu; Dali Gao; Yongjun Feng (Chemical Engineering Journal, 2024)

Short-term exposure to ambient air pollution and hospital admissions for angina among older adults in South China - Luxi Xu; Ruijun Xu; Yunshao Ye; Rui Wang; Jing Wei; Chunxiang Shi; Qiaoxuan Lin; Ziquan Lv; Suli Huang; Qi Tian; Yuewei Liu (Atmospheric Environment, 2024)

LED-driven photocatalytic degradation of tetracycline by chromite ore processing residue (COPR): Mechanism, pathway, toxicity assessment - Shuo Zhang; Cunfang Lu; Yelei Wang; Cheng Tian; Peng Chen; Mingyuan Yang; Min Zhang; Rui Xu; Yuanyuan He; Zilong Li (Journal of Cleaner Production, 2024)

Sulfite activation of Fe-Mn bimetallic oxides for rapid oxidative removal of As(III) in water: Involvement of active Mn(III) - Guiyuan Cai; Yu Tian; Lipin Li; Wenxuan Zhang; Rui Huang; Jun Zhang; Qinyu Wang; Hua Xu; Yifeng Zhang (Chemical Engineering Journal, 2024)

Effect of vane angle on turbulence–chemistry interactions, temperature, flow field, burnout, and NOx emissions in swirling flames fueled by semicoke mixtures - Liutao Sun; Shengyu Kuang; Weilin Li; Jingjie Wang; Yanhui Xu; Lingkun Zhu; Hong Tian; Xinzhuo Li; Dengke Wang; Rui Sun (Environmental Science and Pollution Research, 2023)

Synergistic effect triggered by Fe2O3 and oxygen-induced hydroxyl radical enhances formation of amino-phenolic humic-like substance - Yingchao Zhang; Zhitao Bi; Wenxin Tian; Zhenyu Ge; Yang Xu; Rui Xu; Hongqiong Zhang; Shoufeng Tang (Journal of Environmental Management, 2023)

A review of the toxic effects of ammonia on invertebrates in aquatic environments - Tian-Xu Zhang; Ming-Rui Li; Chen Liu; Shu-Ping Wang; Zhen-Guang Yan (Environmental Pollution, 2023)

A new anchor-siphon drainage combined method used for slope stabilization - Hong-yue Sun; Xu Wang; Yang Yu; Jun-wei Shu; Tian-long Wang; Rui Luo; Zhao-wei Chu (Journal of Mountain Science, 2023)

Characterization of a gE/gI/TK gene-deleted pseudorabies virus variant expressing the Cap protein of porcine circovirus type 2d - Rui-Qin Xu; Lin-Qing Wang; Hui-Hua Zheng; Run-Bo Tian; Lan-Lan Zheng; Shi-Jie Ma; Hong-Ying Chen (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

A novel starch-based ethanol gel with contact-killing bacteria to cut off contact transmission of bacteria - Fu-Xiang Wei; Tian-Rui Zhou; Shao-Wei Zhong; Yong-Fu Deng; Chuan-Hui Xu; Li-Hua Fu; Bao-Feng Lin (Chemical Engineering Journal, 2023)

A multilayer perceptron-based fast sunlight assessment for the conceptual design of residential neighborhoods under Chinese policy - Can Jiang; Xiong Liang; Yu-cheng Zhou; Yong Tian; Shengli Xu; Jia-Rui Lin; Zhiliang Ma; Shiji Yang; Hao Zhou (Building and Environment, 2023)

Farmers’ participation into the recovery of waste agricultural plastic film: An application of the Theory of Planned Behavior - Ze-Ying Zhao; Wen-Bo Li; Peng-Yang Wang; Hong-Yan Tao; Rui Zhou; Jin-Ying Cui; Jian Zhang; Tao Tian; Xu-Zhe Zhao; Yi-Bo Wang; You-Cai Xiong (Waste Management, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Benzene abatement catalyzed by Ceria-Supported platinum nanoparticles and single atoms - Jing Liu; Xue Fang; Daoqing Liu; Xiaolei Hu; Tian Qin; Junxiao Chen; Rui Liu; Dongrun Xu; Weiye Qu; Yangyang Dong; Liwei Chen; Zhen Ma; et al. (Chemical Engineering Journal, 2023)

Circular RNA circAKIRIN2 participates in the process of stress-induced immunosuppression affecting immune response to infectious bursal disease virus vaccine in chicken - Yufei Tian; Xiaoli Ma; Yi Jiang; Jianwei Han; Rui Zhang; Xinxin Xu; Wei Zhang; Chaolai Man (Veterinary Microbiology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Future land-use change and its impact on terrestrial ecosystem carbon pool evolution along the Silk Road under SDG scenarios - Min Cao; Ya Tian; Kai Wu; Min Chen; Yu Chen; Xue Hu; Zhongchang Sun; Lijun Zuo; Jian Lin; Lei Luo; Rui Zhu; Zhenci Xu; et al. (Science Bulletin, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

Magnetic hydrochar derived from waste lignin for thallium removal from wastewater: Performance and mechanisms - Huabin Wang; Ran Duan; Lin Ding; Lin Tian; Ying Liu; Yong Zhang; Rui Xu (Bioresource Technology, 2023)

Reduced plastic film mulching under zero tillage boosts water use efficiency and soil health in semiarid rainfed maize field - Ai-Tian Ren; Ji-Yuan Li; Ling Zhao; Rui Zhou; Jian-Sheng Ye; Yi-Bo Wang; Xu-Cheng Zhang; Kiprotich Wesly; Ming-Sheng Ma; You-Cai Xiong (Resources, Conservation and Recycling, 2023)

Z- scheme heterojunction of BiOI nanosheets grown in situ on NH2-UiO-66 crystals with rapid degradation of BPA in real water - Rui Ji; Zhuzhu Zhang; Lechen Tian; Liujun Jin; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Oxidative stress and inflammation caused by 1-tetradecyl-3-methylimidazolium tetrafluoroborate in rat livers - Huafei Yuan; Feng Xu; Xingxing Tian; Haiyan Wei; Rui Zhang; Yueyue Ge; Hongmei Xu (Environmental Science and Pollution Research, 2022)

Enhancing extracellular electron transfer through selective enrichment of Geobacter with Fe@CN-modified carbon-based anode in microbial fuel cells - Xiao-Long Cheng; Qiang Xu; Qian-Wen Yang; Rui-Rui Tian; Biao Li; Su Yan; Xue-Ying Zhang; Jun Zhou; Xiao-Yu Yong (Environmental Science and Pollution Research, 2022)

Temporal Dynamics in Energy Fluxes and Trophic Structure of a Portunus trituberculatus Polyculture Ecosystem During Different Culture Periods - Jie Feng; Xiang-Li Tian; Shuang-Lin Dong; Rui-Peng He; Kai Zhang; Dong-Xu Zhang; Qing-Qi Zhang (Frontiers in Marine Science, 2022)
Swimming crab ( Portunus trituberculatus ) are an important aquaculture species in eastern coastal areas of China. To improve the understanding of P. trituberculatus culture ecosystem functioning, the dynamics of energy flow and trophic structure of a P. trituberculatus polyculture system (co-culture with white shrimp Litopenaeus vannamei and short-necked clam Ruditapes philippinarum ) were investigated in this study. Three Ecopath models representing the early, middle, and late culture periods of a P. trituberculatus polyculture ecosystem, respectively, were constructed to compare ecosystem traits at different culture periods. The results demonstrated that detritus was the main energy source in this polyculture ecosystem, and most of the total system throughput occurred at trophic levels I and II. Artificial food input and consumption by the culture organisms increased from early to middle and late periods, which produced marked impacts on biomass structure and primary production. R. philippinarum was considered to have a dominant influence on phytoplankton community dynamics which changed from nano- to pico-phytoplankton predominance, from the middle to the late period. Considering the low utilization efficiency of pico-phytoplankton production, large amounts of detritus accumulated in the sediment in the late period, which may constitute a potential risk for the ecosystem. Ecological network analyses indicated that the total energy flow and level of system organization increased from the early to the middle and late periods, whereas food web complexity and system resilience decreased from early to middle and late periods, which may indicate a trend of decreasing ecosystem stability. The system may be further optimized by increased stocking density of R. philippinarum and by introducing macro-algae at a suitable biomass to increase ecosystem stability, energy utilization efficiency, and aquaculture production.

The interplay of particle properties and solution chemistry on aggregation kinetics of soil nanoparticles - Ning Hu; Chen-yang Xu; Zeng-chao Geng; Fei-nan Hu; Qi-rui Li; Ren-tian Ma; Qiang Wang (Journal of Soils and Sediments, 2022)

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

lncRNA SNHG16 Mediates Cell Proliferation and Apoptosis in Cholangiocarcinoma by Directly Targeting miR-146a-5p/GATA6 Axis - Tao Wu; Ming-Sheng Lei; Xu-Zhao Gao; Ting-Gang Xiong; Kang Yang; Qian Gong; Rui Tang; Yue-Peng Tian; Xiao-Hua Fu (Biochemical Genetics, 2021)

A functional chromogen gene C from wild rice is involved in a different anthocyanin biosynthesis pathway in indica and japonica - Weihua Qiao; Yanyan Wang; Rui Xu; Ziyi Yang; Yan Sun; Long Su; Lizhen Zhang; Junrui Wang; Jingfen Huang; Xiaoming Zheng; Shijia Liu; Yunlu Tian; et al. (Theoretical and Applied Genetics, 2021)

Heteroaggregation of humic acid with montmorillonite in divalent electrolytes: effects of humic acid content and ionic concentration - Xiaodan Gao; Yingde Xu; Zhongyi Li; Song Li; Rui Tian; Hang Li; Rattan Lal; Lingzhi Liu; Muhammad Farhan Saeed; Jingkuan Wang (Journal of Soils and Sediments, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Sulfur content in coal formed during different geologic periods in the Guangxi Province and the relationship with the depositional environment - Bohui Xu; Yuxin Song; Yuan Tian; Rui Yang; Fei Xu; Shuli Ding; Pengfei Sun (Arabian Journal of Geosciences, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Digestive characteristics and blood chemistry profile of triploid rainbow trout Oncorhynchus mykiss: influence of body size and seasonal variation - Yuqiong Meng; Buying Han; Changzhong Li; Kangkang Qian; Xiaohong Liu; Xuemin Hu; Xu Yang; Haining Tian; Rui Ma (Fisheries Science, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Long noncoding RNA UCA1 promotes the proliferation of hypoxic human pulmonary artery smooth muscle cells - Tian-Tian Zhu; Rui-Li Sun; Ya-Ling Yin; Jin-Ping Quan; Ping Song; Jian Xu; Ming-Xiang Zhang; Peng Li (Pflügers Archiv - European Journal of Physiology, 2019)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Composition and antimicrobial activity of the essential oil from the branches of Jacaranda cuspidifolia Mart. growing in Sichuan, China - Juanjuan Yuan; Tian Gan; Yingtian Liu; Hui Gao; Weifeng Xu; Tao Zhang; Rui Tan; Zhenghong Cai; Hezhong Jiang (Natural Product Research, 2018)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Characterization of uncultivated magnetotactic bacteria from the sediments of Yuehu Lake, China - Haijian Du; Rui Zhang; Wenyan Zhang; Cong Xu; Yiran Chen; Hongmiao Pan; Ke Zhou; Long-fei Wu; Tian Xiao (Acta Oceanologica Sinica, 2017)

Curdlan blocks the immune suppression by myeloid-derived suppressor cells and reduces tumor burden - Ke Rui; Jie Tian; Xinyi Tang; Jie Ma; Ping Xu; Xinyu Tian; Yungang Wang; Huaxi Xu; Liwei Lu; Shengjun Wang (Immunologic Research, 2016)

Upregulation of long noncoding RNA TMEVPG1 enhances T helper type 1 cell response in patients with Sjögren syndrome - Juan Wang; Huiyong Peng; Jie Tian; Jie Ma; Xinyi Tang; Ke Rui; Xinyu Tian; Yungang Wang; Jianguo Chen; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2016)

Decreased expression of microRNA-125a-3p upregulates interleukin-23 receptor in patients with Hashimoto’s thyroiditis - Huiyong Peng; Yingzhao Liu; Jie Tian; Jie Ma; Xinyi Tang; Jun Yang; Ke Rui; Yue Zhang; Chaoming Mao; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2015)

Ribosomal Protein L3 Mutations are Associated with cfr-Mediated Linezolid Resistance in Clinical Isolates of Staphylococcus cohnii - Hongtao Xu; Rui Tian; Yanming Li; Dongke Chen; Yalin Liu; Yunjian Hu; Fei Xiao (Current Microbiology, 2015)

GITRL as a genetic adjuvant enhances enterovirus 71 VP1 DNA vaccine immunogenicity - Jing Yuan; Xinyi Tang; Kai Yin; Jie Tian; Ke Rui; Jie Ma; Chaoming Mao; Jianguo Chen; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2015)

Estimations of net primary productivity and evapotranspiration based on HJ-1A/B data in Jinggangshan city, China - Rong-hua Zhang; Rui Sun; Jun-ping Du; Ting-long Zhang; Yao Tang; Hong-wei Xu; Sheng-tian Yang; Wei-guo Jiang (Journal of Mountain Science, 2013)

Cloning, characterization and expression of the LECT2 gene in grass carp - Tian Yuan; Chuang Li; Ji-Rui Gu; Yue-Jun Fu; Heng Xu (Fish Physiology and Biochemistry, 2013)

Involvement of dopamine D2 receptors activation in ischemic post-conditioning-induced cardioprotection through promoting PKC-ε particulate translocation in isolated rat hearts - Jun Gao; Jin Guo; Hongxia Li; Shuzhi Bai; Hong Li; Bo Wu; Lina Wang; Yuhui Xi; Ye Tian; Guangdong Yang; Rui Wang; Lingyun Wu; et al. (Molecular and Cellular Biochemistry, 2013)

Isolation and characterization of fifteen novel microsatellite loci in golden mandarin fish (Siniperca scherzeri) Steindachne - Min Yang; Xu-Fang Liang; ChangXu Tian; Yasmeen Gul; YaQi Dou; Liang Cao; Rui Yu (Conservation Genetics Resources, 2012)

Involvement of calcium-sensing receptor in oxLDL-induced MMP-2 production in vascular smooth muscle cells via PI3K/Akt pathway - Hong-Xia Li; Fan-Juan Kong; Shu-Zhi Bai; Wen He; Wen-Jing Xing; Yu-Hui Xi; Guang-Wei Li; Jin Guo; Hong-Zhu Li; Ling-Yun Wu; Rui Wang; Guang-Dong Yang; et al. (Molecular and Cellular Biochemistry, 2012)

Molecular and serological diversity in Apple chlorotic leaf spot virus from sand pear (Pyrus pyrifolia) in China - Yansu Song; Ni Hong; Liping Wang; Hongju Hu; Rui Tian; Wenxing Xu; Fang Ding; Guoping Wang (European Journal of Plant Pathology, 2011)

Multiple amino acid variations in the nonstructural proteins of swine Japanese encephalitis virus alter its virulence in mice - Rui Wu; Yongxiang Tian; Junhua Deng; Keli Yang; Wangwang Liang; Rui Guo; Zhengying Duan; Zewen Liu; Danna Zhou; Diping Xu (Archives of Virology, 2011)

Molecular cloning, characterization and expression analysis of adenylosuccinate lyase gene in grass carp (Ctenopharyngodon idella) - Tian Yuan; Ji-Rui Gu; Wen-Bo Gu; Jiang Wu; Shao-Rong Ge; Heng Xu (Molecular Biology Reports, 2011)

Human Prion Protein Mutants with Deleted and Inserted Octarepeats Undergo Different Pathways to Trigger Cell Apoptosis - Kun Xu; Xin Wang; Qi Shi; Cao Chen; Chan Tian; Xiao-Li Li; Rui-Min Zhou; Yong-Lie Chu; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Microbial community structure and diversity in a native forest wood-decomposed hollow-stump ecosystem - Bao-Yu Tian; Qin-Geng Huang; Yan Xu; Chun-Xiang Wang; Rui-Rui Lv; Jian-Zhong Huang (World Journal of Microbiology and Biotechnology, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Chemical constituents from the fruits of Hippophae rhamnoides - Rui-Xia Zheng; Xu-Dong Xu; Ze Tian; Jun-Shan Yang (Natural Product Research, 2009)

Deglycosylation altered the gating properties of rNav1.3: glycosylation/deglycosylation homeostasis probably complicates the functional regulation of voltage-gated sodium channel - Qing Xu; Hui-Wen Cheng; Hui-Qiong He; Zhi-Rui Liu; Ming He; Hong-Tian Yang; Zhi-Lei Zhou; Yong-Hua Ji (Neuroscience Bulletin, 2008)

Functional response of the predator Scolothrips takahashii to hawthorn spider mite, Tetranychus viennensis: effect of age and temperature - Li Ding-Xu; Tian Juan; Shen Zuo-Rui (BioControl, 2007)